BENTUK SAJIAN BEDHAYA SAPTONGKARA KARYA I NYOMAN CAHYA BERSAMA SULISTYO HARYANTI - Renansia, Erika Meilanawati; Setyoasih, Sri (Greget: Jurnal Kreativitas dan Studi Tari, 2022)
This article explores a unique form of group dance known as Bedhaya, which conveys symbolic expression through movement. The dance utilizes the symbol of Sapta Ongkara, representing the energy within humans and the universe. The Bedhaya Saptongkara dance was created by two choreographers, I Nyoman Chaya and Sulistyo Haryanti, in 2019. To delve deeper into the form and structure of this Bedhaya dance, the study employs Y. Sumandiyo Hadi's theory, which is instrumental in detailing the dance's elements. The study successfully produces a comprehensive description of the movement composition in the Bedhaya Saptongkara dance, meticulously crafted by I Nyoman Chaya and Sulistyo Haryanti. This description encompasses various crucial aspects of Bedhaya dance, including the dance movements, themes presented, type of dance, mode of presentation, the number and gender of the dancers, the dance space and stage, accompanying music, makeup and costumes of the dancers, props used, and the lighting that enhances the entire performance. Thus, this article provides an in-depth and structured overview of the Bedhaya Saptongkara dance, illustrating how the Sapta Ongkara symbol is embodied within the richly meaningful and philosophical artistic elements of the dance.